Topology optimization of 3D-printed continuous fiber-reinforced composites considering manufacturability - Yang, Zhe; Fu, Kunkun; Zhang, Zhongsen; Zhang, Junming; Li, Yan (Composites science and technology, 2022)
This work presented an orthogonal-element solid orthotropic material with penalization (SOMP) topology optimization method incorporating with 3D printing manufacturability of continuous carbon fiber reinforced composites (CCFRCs), together with a printing path planning strategy. Topological optimizations were performed with a shear beam and a bending beam to demonstrated the effectiveness of the proposed method. The optimal structure was also determined by a traditional density-based SOMP topology optimization method with an offset path planning method for comparison. The results showed that the printing paths of the optimal structure were consistent with the fiber orientation distribution of the optimal results by the proposed orthogonal-element SOMP method. Correspondingly, the stiffness and the stiffness-to-weight ratio of the optimal specimen by the presented orthogonal-element SOMP method were increased by 30.0% and 26.3%, respectively, compared with those by the traditional SOMP method. In addition, the low void contents inside the optimal specimens also confirmed the effectiveness of the proposed orthogonal-element SOMP method with the consideration of the manufacturability. [Display omitted] •An orthogonal-element SOMP method for CCFRP is proposed considering manufacturability.•Structural stiffness after this optimization is greater than those by traditional SOMP method.•Consistency between print path and fiber orientation is seen in printed specimen with low void content.